Evaluation of the Antibacterial Effects of Flavonoid Combination from the Leaves of Dracontomelon dao by Microcalorimetry and the Quadratic Rotary Combination Design - Li, Yang; Xia, Houlin; Wu, Mingquan; Wang, Jiabo; Lu, Xiaohua; Wei, Shizhang; Li, Kun; Wang, Lifu; Wang, Ruilin; Zhao, Pan; Zhao, Yanling; Xiao, Xiaohe (Frontiers in Pharmacology, 2017)
Skin infectious disease is a common public health problem due to the emergence of drug-resistant bacteria caused by the antibiotic misuse. Dracontomelon dao (Blanco) Merr. et Rolfe, a traditional Chinese medicine, has been used for the treatment of various skin infectious diseases over thousands of years. Previous reports have demonstrated that the leaves of Dracontomelon dao present favorable antibacterial activity against Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus and Bacillus subtitles. The flavonoids are the main components of the ethyl acetate extract of Dracontomelon dao leaf. However, the correlation between flavonoids and antibacterial activities is yet to be determined. In this study, the combined antibacterial activities of these flavonoids were investigated. Three samples with the different concentrations of flavonoids (S1-S3) were obtained. By microcalorimetric measurements, the results showed that the IC50 value of S2 was lower than those of S1 and S3. The contents of main flavonoids (including Luteolin, L-Epicatechin, Cianidanol and Quercetin) in S1-S3 were various, confirmed by the method of the Ultra High Performance Liquid Chromatography (UPLC). Based on the method of quadratic general rotary unitized design, the antibacterial effect of single flavonoid, and the potential synergistic effects between Luteolin and Quercetin, Luteolin and Cianidanol were calculated, which were also proved by microcalorimetric analysis. The antibacterial activities of main flavonoids were Luteolin > Cianidanol > Quercetin > L-Epicatechin. Meanwhile, the synergistic effects of Luteolin and Cianidanol (PL+C = 1.425), Quercetin and Luteolin (PL+Q = 1.129) on anti-microbial activity were validated. Finally, we found that the contents of Luteolin, L-Epicatechin, Cianidanol, Quercetin were 1061.00~1061.00, 189.14~262.86, 15990.33~16973.62, 6799.67~7662.64 ng·ml-1 respectively, with the antibacterial rate over 60.00 %. In conclusion, this study could provide reference for quality evaluation and pharmacodynamics research of Dracontomelon dao.